Workplace bullying and subsequent sleep problems - the Helsinki Health Study - Tea Lallukka; Ossi Rahkonen; Eero Lahelma (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVE: The associations between workplace bullying and subsequent sleep problems are poorly understood. This study aims to address this evidence gap. METHODS: We used the Helsinki Health Study questionnaire survey data at baseline in 2000-2002 and follow-up in 2007 (N=7332). The 4-item Jenkins sleep questionnaire was used in both surveys. Two measures of workplace bullying asked whether the respondent had (i) reported being bullied and (ii) observed bullying. Logistic regression models were fitted, adjusting for age, childhood bullying, education, working conditions, obesity, common mental disorders, limiting long-standing illness, and baseline sleep problems. RESULTS: At baseline, 5% of women and men reported being currently bullied. Additionally, 9% of women and 7% of men had frequently observed bullying at their workplace. Adjusted for age, reporting bullying was associated with sleep problems at follow-up among women [odds ratio (OR) 1.69, 95% confidence interval (95% CI) 1.30-2.20) and men (OR 3.17, 95% CI 1.85-5.43). Also, reporting earlier bullying was associated with sleep problems among both women (OR 1.47, 95% CI 1.26-1.72) and men (OR 1.58, 95% CI 1.06-2.36). Separate adjustments for covariates had some effects on the associations. After full adjustment for childhood bullying and baseline sociodemographic factors, working conditions, health, and sleep problems, the associations reduced. Similarly, adjusted for age, observing bullying was associated with sleep problems among women (OR 2.00, 95% CI 1.61-2.48) and men (OR 2.04, 95% CI 1.23-3.39). CONCLUSIONS: Workplace bullying is associated with sleep problems, but associations attenuate after factors related to the social environment, work, and health are simultaneously taken into account.